Dissertações defendidas no Programa de Pós-graduação em Geografia/UFMG no 2º semestre de 2016 (Revista Geografias, 2022)
Dissertações defendidas no Programa de Pós-graduação em Geografia/UFMG no 2º semestre de 2016